Importance of genetics in acute myeloid leukemia - Pippa, R.; Odero, M. D. (Anales del Sistema Sanitario de Navarra, 2014)
Acute myeloid leukemia (AML) comprises a biologically and clinically heterogeneous group of aggressive disorders that occur as a consequence of a wide variety of genetic and epigenetic abnormalities in hematopoietic progenitors. Despite significant advances in the understanding of the biology of AML, most patients will die from relapsed disease. Whole-genome studies have identified novel recurrent gene mutations with prognostic impact in AML; furthermore, it is likely that in the near future genome-wide sequencing will become a routine for newly diagnosed patients with AML. Therefore, future clinical trials should aim to identify genetically defined high-risk patients, and further research is necessary to identify effective agents and develop new individualized therapeutic strategies for the treatment of this deadly disease.